Revitalizing Millenial Spirituality: A Study on the Dynamics of Urban Sufism in the Copler Community of Surabaya - Wulandari, Nadiya Safitri; Damanhuri (Faculty of Ushuluddin and Philosophy, 2023)
This article examines the dynamics of urban Sufism in the millennial era through a case study of the Copler Community in Surabaya led by Gus Muhammad Nur el-Yaqin al-Ishaqi (Gus Nico). Using a qualitative case study method, this research explores the adaptation of Sufi teachings in facing the challenges of modernity and changes in the lifestyle of urban youth. Data was collected through participatory observation, in-depth interviews, and a literature review. The findings reveal that urban Sufism serves as a strategic alternative in fostering religiosity amid the dominance of instant and secular culture. The Copler Community functions as a transformative space where practices such as dhikr, reading manāqib, and mawlid are integrated with a communicative approach that resonates with the younger generation. Participation in these activities contributes significantly to behavioral changes among community members, strengthening spiritual bonds and social solidarity. These findings emphasize the importance of urban Sufism as a form of spiritual revitalization in the context of modern urban life and open new possibilities for more inclusive and contextual approaches to da‘wah among millennials.